P227 Perceived stress and socioeconomic factors associated with vaginal microbiota in the longitudinal study of vaginal flora. (14th July 2019) - Turpin, Rodman; Slopen, Natalie; He, Xin; Robinson, Courtney; Klebanoff, Mark; Ravel, Jacques; Brotman, Rebecca
Abstract : Background: Lactobacillus -dominated vaginal microbiota can confer protection against STIs and high levels of stress and lower socioeconomic status are associated with increased risk for STIs. We examined whether perceived stress and demographic factors are associated with vaginal microbiota. Methods: A subsample of women (n=1, 595) enrolled in the Longitudinal Study of Vaginal Flora (LSVF) were utilized in this study. Vaginal microbiota was characterized by amplicon sequencing of the V3-V4 hypervariable regions of the 16S rRNA gene and clustered into community state types (CSTs). Stress in the past 30 days was measured using the Perceived Stress Scale and was categorized into quartiles. We used mixed-effects multinomial regression models accounting for within-subject associations to compare prevalence of Lactobacillus iners -dominated (CST III) and low- Lactobacillus (CST IV) versus a category of high relative abundance of other Lactobacillus spp. (CST I, II, V) across stress quartiles and demographics including education, income, race, marital status, and age. Results: In unadjusted models, the third stress quartile (reference first quartile) was associated with greater prevalence of CST III (prevalence ratio (PR=1.15, p=0.013) and IV (PR=1.22, p=0.048). The top quartile of stress was not statistically significant. After adjusting for covariates, results were attenuated. An education below high school level (reference high school or more) was associated with higher prevalence of CST III (PR=1.30, p=0.002) and IV (PR=1.35, p=0.002). Lower prevalence of CST IV was observed among participants who were White (reference Black, PR=0.38, p<0.001), and had >$3000 monthly income (reference <$500, PR=0.80, p=0.47). Conclusion: In bivariate analysis, moderate stress levels were associated with less optimal vaginal microbiota, exemplified by low abundance of Lactobacillus and L. iners -dominated microbiota. Adjustment for education and income attenuated these findings. Future studies are needed to clarify how education and income associated with vaginal microbiota, whether through access to care, sexual networks or stress affecting the body's immune response. Disclosure: No significant relationships.